2015
DOI: 10.4161/21645515.2014.990851
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of two different assay kits for the detection of secreted alkaline phosphatase in HPV antibody neutralization assays

Abstract: TM SEAP Chemiluminescence Kit 2.0; ELISA, enzyme-linked immunosorbent assay; GFP, green fluorescent protein; L1 and L2, late 1 and late 2 proteins; RLU, relative-light-unitTo assess immunogenicity and development of antibodies in the context of vaccination, it is critical to quantify titers of neutralizing antibodies. We have been employing the 293TT cell-based neutralization assay system to quantify anti-HPV neutralizing antibodies. In this system, human papillomavirus (HPV) pseudovirion (PsV) particles encap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Also, the amount of HPV16 and HPV18 PsV particles required to infect 293TT cells to achieve 100-fold induction in signal over the background was at least 10-fold less with Ziva ® . Neutralizing anti-L1 antibody titers we measured by Ziva ® and Great EscAPe™ in sera of Cervarix ® (GlaxoSmithKline) vaccinated individuals were virtually identical, suggesting that Ziva ® can be a suitable alternative to the well-established Great EscAPe (Kemp et al, 2015)…”
Section: Commentarymentioning
confidence: 84%
See 1 more Smart Citation
“…Also, the amount of HPV16 and HPV18 PsV particles required to infect 293TT cells to achieve 100-fold induction in signal over the background was at least 10-fold less with Ziva ® . Neutralizing anti-L1 antibody titers we measured by Ziva ® and Great EscAPe™ in sera of Cervarix ® (GlaxoSmithKline) vaccinated individuals were virtually identical, suggesting that Ziva ® can be a suitable alternative to the well-established Great EscAPe (Kemp et al, 2015)…”
Section: Commentarymentioning
confidence: 84%
“…This L1‐PBNA system measures HPV anti‐L1 antibody titers using PsV particles where little or no L2 proteins on the virion have been cleaved. Using this system, we compared the Clontech's Great EscAPe SEAP Chemiluminescence Kit 2.0 and Jaden Bioscience's Ziva Ultra SEAP Plus Detection Kit (Kemp et al., ). When we compared these 2 kits, we found that Ziva was able to provide higher signals than those of the Clontech's kit.…”
Section: Commentarymentioning
confidence: 99%
“…Many reporter genes can be used to construct the replicon of pseudovirus, such as EGFP, SEAP, β‐gal, luciferase . The report gene can be activated in 30 min and express large amount of exogenous protein in case of virus entry.…”
Section: Discussionmentioning
confidence: 99%